Credit frictions, selection into external finance, and gains from trade - Florian Unger (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper analyzes the effects of credit frictions in a trade model where heterogeneous firms select both into exporting and into two types of external finance. In our framework, small producers face stronger credit frictions, pay a higher borrowing rate and rely on bank finance, whereas large firms have access to cheaper bond finance. We show that an increase in credit frictions induces firms to select into bank finance, which attenuates the negative implications on product variety and welfare. In the open economy, the presence of effective financial intermediation increases the welfare gains from trade. In a counterfactual analysis, we exploit that our framework nests a model with credit frictions and one type of finance as a special case, and we show that endogenous selection into external finance is an important channel of adjustment.
Keywords: F12; G32; L11; 330; international trade; external finance; credit constraints; heterogeneous firms; moral hazard; bank and bond finance